BIOPROSPEKSI POTENSI AKTINOBAKTERI HALOFILIK SEBAGAI ANTIBAKTERI PATOGEN PADA MANUSIA DARI TAMBAK GARAM TALISE SULAWESI TENGAH - Nurfadilah; Salsabila, Rani; Saskirana; Ifandi, Slamet; Inayah, Nur; Arumdani, Salsabila; Lindhemutianingrum Siradje, Andi (Universitas Cokroaminoto Palopo, 2025)
This study aims to explore the potential of halophilic actinobacteria from Talise salt ponds, Central Sulawesi, as candidates for producing antibacterial compounds. The study was conducted through isolation, macroscopic and microscopic characterization, biochemical tests, and testing of antibacterial activity against S. aureus and E. coli using the disc diffusion method. Data were analyzed descriptively based on observations and inhibition zone measurements. The results showed the acquisition of five halophilic actinobacteria isolates, namely TL1, TL2, TL3, TL4, and TL5, which have characteristics similar to the genus Streptomyces. Biochemical tests indicated unique metabolic capabilities, including the production of the catalase enzyme and sugar utilization in the TSIA test. All isolates showed antibacterial activity, with isolate TL5 providing the largest inhibition zone, namely 16.5 mm against E. coli and 6.5 mm against S. aureus. These findings indicate that halophilic actinobacteria from Talise salt ponds have the potential to be a source of new antibiotics relevant for drug development in addressing antibiotic resistance